Synergetic effects of alternative fuels on compression-ignition engines: potential of ethanol and fischer-tropsch diesel blends - Torres, Felipe Andrade (2021)
Nowadays, research interest related to the application of alternative fuels, such as ethanol, to mitigate the utilization of fossil diesel fuel is increasing. Furthermore, another potential non-conventional fuel is the Fischer-Tropsch (F-T) diesel, which is a synthesized fuel that may also be produced from biomass. However, as the miscibility between these two biofuels is limited, thus, another biofuel was considered to promote the blend stability, the biodiesel. The present work aimed to propose a blend of alternative fuels and investigate the effects of the mixture on a diesel engine's combustion, exhaust emissions, particulate matter characteristics, the performance of an aftertreatment system, as well as an exergetic analysis. Ethanol, F-T diesel, and biodiesel were blended in the volumetric fractions of 15, 50, and 35%, respectively (FTD50E15B35). A single-cylinder diesel engine equipped with a common-rail injection system was used to test this blend and compare the results with diesel and a blend of ethanol, diesel, and biodiesel in these same volumetric fractions (D50E15B35). It was shown that F-T diesel and ethanol could be combined to conform with the current fuel standards provided that biodiesel is added to the mixture. FTD50E15B35 reduced the regulated emissions of THC, NO, and PM, however, with a penalty in CO emissions in comparison with diesel fuel. The heavy-hydrocarbons decreased, whilst the light-hydrocarbons increased in comparison with diesel. The unregulated emissions, N2O, NH3, and HNCO, decreased for the blends, although CH2O slightly increased. Besides, the diesel oxidation catalyst (DOC) has effectively reduced the levels of CO, THC, and NO in the exhaust. However, the DOC light-off temperatures of the blends were shifted to higher values. Further, the total particle number and mass concentrations of FTD50E15B35 were lower than for D50E15B35 and diesel. Further, the energy and the exergy efficiencies were found to be similar, around 26% and 24%, respectively. Both energy and exergy efficiencies of FTD50E15B35 were slightly lower than for diesel fuel. It was concluded that ethanol, F–T diesel, and biodiesel have individual properties that, when combined, have a potential for particulate emission-reducing along with aftertreatment systems and injection strategies promoting benefits for the engine combustion, as future emissions legislation standards are foreseen to be more stringent.